Some extensions of Bateman's product formulas for the Jacobi polynomials. (1995) - Chen, Ming-Po; Srivastava, H. M.
Abstract : The authors derive generalizations of some remarkable product formulas of Harry Bateman (1882-1946) for the classical Jacobi polynomials. They also show how the results considered here would lead to various families of linear, bilinear, and bilateral generating functions for the Jacobi and related polynomials.